Potential Predictors of Cardiovascular Risk Improvement in Patients with Hidradenitis Suppurativa Treated with Adalimumab: A Pivotal Study of Factors Associated with Carotid Intima-Media Thickness Reduction - Manuel Sánchez-Díaz; Luis Salvador-Rodríguez; Carlos Cuenca-Barrales; Salvador Arias-Santiago; Alejandro Molina-Leyva (Adis, Springer Healthcare, 2023)
Abstract Introduction Hidradenitis suppurativa (HS) has been linked to higher cardiovascular risk (CVR) due to its inflammatory burden. There is little evidence on how biologic treatment could modify the cardiovascular risk of patients with HS. The aims of the present study were to explore the modification of CVR in patients under adalimumab treatment and to explore the potential factors associated with CVR improvement. Methods A prospective longitudinal study was performed. A cohort of patients with HS treated with adalimumab was followed up. Carotid intima-media thickness (IMT) and other clinical and biochemical CVR factors were collected at baseline and 32 weeks after starting the treatment. Results Twenty-seven patients with severe HS were included. Overall, there were no differences in IMT between baseline (633 μm) and 32 weeks follow-up (634 μm). However, 40.7% (11/27) of the patients presented an improvement in IMT. This group (IMT responders) had a higher prevalence of dyslipidemia, diabetes mellitus, higher HbA1c levels, consumed more tobacco, and had higher BMI at baseline. Moreover, these patients had lower IHS4 scores at baseline and tended to have a greater IMT basal value, indicating a higher burden of subclinical atherosclerosis. Conclusions Adalimumab treatment might benefit a subset of patients with HS in terms of cardiovascular risk reduction. In light of the results of the present study patients with classical cardiovascular risk factors, and those with higher burden of subclinical atherosclerosis and with less inflammatory load, may be more likely to improve their IMT during adalimumab treatment.